100 years since Blagovest Dolapchieff birth - Hristov, E. (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2008)
The main facts and dates in the biography of the well-known bulgarian scientist B. Dolaptschieff are given.